14 Neurobehavioural characteristics of limbic encephalitis associated with voltage-gated potassium channel complex antibodies. Issue 8 (13th July 2017) - Loane, Clare; Roca-Fernandez, Adriana; Lage-Martinez, Carmen; Ahmed, Samrah; Butler, Chris R
Abstract : Objective: Limbic encephalitis associated with antibodies to the voltage-gated potassium channel complex (VGKC-LE) often results in memory impairment with accompanying hippocampal damage thus potentially providing a robust human model of hippocampal amnesia. However, comprehensive characterisation of the neurobehavioural profile of VGKC-LE patients is currently lacking. We aim to provide a detailed description of the clinical outcome of these patients as well as determine whether they are indeed a useful model for hippocampal amnesia studies. Method: A group of VGKC-LE patients (n=17) and matched controls underwent clinical interview and extensive neuropsychology testing covering multiple cognitive domains. Structural magnetic resonance imaging (MRI) and resting-state functional MRI (rs-fMRI) was acquired in all subjects. Investigation of atrophy profiles was completed via manual delineation of medial temporal lobes (MTL) structures and FreeSurfer cortical parcellation using non-parametric permutation testing. Rs-fMRI data were analysed using both independent component analysis (ICA) and seed-based connectivity analysis (SBCA) to investigate aberrant functional connectivity of the default mode network (DMN) and anterior and posterior memory networks. Associations between memory performance and structure and functional measures were investigated. Results: The neuropsychological profile indicates memory function is preferentially affected whereas non-memory function is spared. Moreover, recall memory (recall composite; p<0.01) appears to be more affected than recognition memory (faces, p=0.24; words, p=0.1; scenes, p<0.01). Structural MRI analyses confirms focal hippocampal atrophy with no evidence for a consistent reduction of other sub-cortical or cortical regions. No significant association between hippocampal atrophy and memory performance was detected. ICA analysis failed to detect significant DMN differences in patients vs. controls both at the whole DMN network and within DMN network level. SBCA demonstrated reduced functional connectivity evident from anterior hippocampi to each contralateral temporal pole. Functional connectivity between left anterior hippocampus and right temporal pole was significantly correlated with WMS-IV Word List delayed recall scores (r=−0.584; p=0.05) in patients. Conclusions: We have demonstrated that VGKC-LE patients present with persistent memory impairment in line with a previous retrospective study (Butler et al., 2014; JNNP). We also demonstrate that VGKC-LE patients have focal hippocampal atrophy supporting the use of patients with limbic encephalitis as a human model of hippocampal amnesia. However, the presence of hippocampal atrophy alone does not clearly explain the memory deficits. Instead, our data strongly suggest that a functional disturbance at rest is a contributory factor and could explain inconsistencies currently existing in the hippocampal amnesia literature.